Reconfigurable Intelligent Surfaces (RIS) and Their Role in Next‐Generation Wireless Networks: An Overview - Nwufo, Chukwuemeka; Simpson, Oluyomi; Sun, Yichuang (Transactions on emerging telecommunications technologies, 2025)
ABSTRACT Extensive research is now peering into the next generation of wireless technology. The significant talking points are how to effectively manage scarce wireless resources with the spiraling amount of wireless data traffic and the exponential growth of the number of nodes occupying the wireless communication ecosystem. Giant performance strides are offered by promising state‐of‐the‐art technologies, such as Massive MIMO and mm‐Wave technology, in tackling this resource scarcity problem; however, their application has proven prohibitive. Given its energy‐efficient and low‐cost characteristics, RIS has emerged as a promising technique for the beyond 5G networks. Furthermore, when deployed in a wireless communication scenario, the passive nature also means it can reliably extend network coverage and enhance spectral efficiency and security in the physical layer. This paper presents an in‐depth overview of the background of RIS, its applications, and use cases, especially concerning wireless communications. This paper also touches on the RIS application to wireless communication networks and its combination with other emergent wireless technologies such as NOMA, SWIPT, UAVs and autonomous vehicles. Finally, a comparative case study was presented in which comparisons were drawn out for RIS‐aided communication and relay‐aided communication, with direct communication as a benchmark. This paper explicitly reviews the state‐of‐the‐art RIS‐assisted wireless networks, especially open challenges relating to the B5G and 6G networks. This work presents an intensive study of recent research on RIS to provide an in‐depth understanding of the underlying principles surrounding RIS operations, composition, and effect on EM waves.